Oxidation demetallization of heavy metals in petroleum heavy crude oil - Ihsan wan Azelee, 1989-; Razali Ismail, supervisor; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2011